Radiotherapy Role in Rectal Cancer at Prof. Dr. R. D. Kandou General Hospital, Manado, Indonesia - Jeffri Jeffri; Ferdinand Tjandra; Michael Tendean; Toar Mambu; Enrico Napitupulu (Medical Scope Journal, 2023)
Abstract: Rectal cancer (RC) remains as a major health burden, being the 3rd most common form of cancer and leading cause of death. RC effects as much as 12.8 per 100 adult population with a mortality rate as high as 9.5%.1 Efforts were made to reduce morbidity and mortality due to rectal cancer. One of them is radiotherapy acting as both neoadjuvant and adjuvant. Thus study aimed to emphasize the role of radioteraphy in treating rectal cancer patients at Prof. Dr. R. D. Kandou General Hospital, Manado. This was a retrospective study using data of all rectal cancer outpatients seeking at Prof. Dr. R. D. Kandou General Hospital, Manado. from 2017-2020 especially of those receiving radiotherapy treatment in radiology department. The results obtained a total 119 patients, 28 of them received radiotherapy based on staging and clinical judgement. From the radiotherapy group, 46.4% patient received neoadjuvant radiotherapy primary to surgical procedure, and among the neoadjuvant group 71.4% received long course radiotherapy. From the neoadjuvant radiotherapy group, 46.4% became resectable and 46.4% among them underwent Miles Procedure. In conclusion, rectal cancer is still a health problem, and radiotherapy as one of the modality play major role as neoadjuvant and adjuvant treatment.